Validity and Reliability of the Turkish Version of the 8-Item Parkinson’s Disease Questionnaire - Kahraman, Turhan (Noro Psikiyatr Ars, 2018)
INTRODUCTION: Symptomatic control and improvement of health-related quality of life (HRQoL) is a key feature of the management of patients with Parkinson’s disease (PD). The 39-item Parkinson’s Disease Questionnaire (PDQ) and its short version, PDQ-8, validated disease-specific patient-reported instruments, have been highly recommended to use for assessing HRQoL in patients with PD. The aim of this study was to assess the reliability and validity of the Turkish version of the PDQ-8. METHODS: Eighty-three patients with PD were recruited for this methodological and cross-sectional study. The PDQ-8 was repeated to assess the test-retest reliability after one-week interval. The participants completed the 36-Item Short Form Health Survey (SF-36) as a generic HRQoL previously validated in Turkey. The Hoehn & Yahr stages of the patients were also determined. The SF-36 and Hoehn & Yahr stages were used to assess the convergent validity of the PDQ-8. RESULTS: The Cronbach’s alpha coefficient was 0.78 (95% CI: 0.70–0.84, p<0.001) for PDQ-8. The test-retest reliability was very high as the intra-class correlation coefficient was 0.97 (95% CI: 0.93–0.99, p<0.001). The PDQ-8 had significant correlations with the physical and mental component scores of SF-36 (ρ=-0.52, p<0.001 and ρ=-0.64, p<0.001, respectively) and Hoehn & Yahr stages (ρ=0.56, p<0.001). There was no evidence of floor or ceiling effects. CONCLUSION: The results of this study suggest that the Turkish version of the PDQ-8 is a reliable, valid, less time-consuming, and brief disease-specific instrument to assess HRQoL in patients with Parkinson’s disease.